GE_GERICHTE A/3733/2024 vom 12. November 2024 - GE Cour de justice (2024)
DÉTENTION AUX FINS D'EXPULSION;PROPORTIONNALITÉ | LEI.75.al1.letb; LEI.75.al1.letc; LEI.76.al1.letb.ch3; LEI.73.al1.letb.ch4; LEI.79.al2